Retinofugal pathways in fetal and adult spiny dogfish, Squalus acanthias - Northcutt, R. Glenn (Brain Research, 1979)
Retinofugal pathways in fetal and adult spiny dogfish were determined by intraocular injection of [3H]proline for autoradiography. Distribution and termination of the primary retinal efferents were identical in pups and adults. The retinal fibers decussate completely, except for a sparse ipsilateral projection to the caudal preoptic area. The decussating optic fibers terminate ventrally in the preoptic area and in two rostral thalamic areas, a lateral neuropil area of the dorsal thalamus and more ventrally in the lateral half of the ventral thalamus. At this same rostral thalamic level, a second optic pathway, the medial optic tract, splits from the lateral marginal optic tract and courses dorsomedially to terminate in the rostral tectum and the central and periventricular pretectal nuclei. The marginal optic tract continues caudally to terminate in a superficial pretectal nucleus and also innervates the superficial zone of the optic tectum. A basal optic tract arises from the ventral edge of the marginal optic tract and courses medially into the central pretectal nucleus, as well as continuing more caudally to terminate in a dorsal neuropil adjacent to nucleus interstitialis and in a more ventrally and medially located basal optic nucleus.Comparison of the retinofugal projections of Squalus with those of other sharks reveals two grades of neural organization with respect to primary vusula projections. Squalomorph sharks possess a rostral dorsal thalamic nucleus whose visual input is primarily, if not solely, axodendritic, and an optic tectum in which the majority of the cell bodies are located deep to the visual terminal zone. In contrast, galeomorph sharks are characterized by an enlarged and migrated rostrodorsal thalamic visual nucleus, and an optic tectum in which the majority of the cell bodies are located within the visual terminal zone. These data suggest that evolution of primary visual pathways in sharks occurs by migration and an increase in neuronal number, rather than by the occurence of new visual ...